Non-Thermal Irreversible Electroporation (N-TIRE) and Adjuvant Fractionated Radiotherapeutic Multimodal Therapy for Intracranial Malignant Glioma in a Canine Patient - Garcia, P. A. (Technol Cancer Res Treat, 2011)
Non-thermal irreversible electroporation (N-TIRE) has shown promise as an ablative therapy for a variety of soft-tissue neoplasms. Here we describe the therapeutic planning aspects and first clinical application of N-TIRE for the treatment of an inoperable, spontaneous malignant intracranial glioma in a canine patient. The N-TIRE ablation was performed safely, effectively reduced the tumor volume and associated intracranial hypertension, and provided sufficient improvement in neurological function of the patient to safely undergo adjunctive fractionated radiotherapy (RT) according to current standards of care. Complete remission was achieved based on serial magnetic resonance imaging examinations of the brain, although progressive radiation encephalopathy resulted in the death of the dog 149 days after N-TIRE therapy. The length of survival of this patient was comparable to dogs with intracranial tumors treated via standard excisional surgery and adjunctive fractionated external beam RT. Our results illustrate the potential benefits of N-TIRE for in vivo ablation of undesirable brain tissue, especially when traditional methods of cytoreductive surgery are not possible or ideal, and highlight the potential radiosensitizing effects of N-TIRE on the brain.